Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Ghani, A.A.; Hazad, F.I.; Jamil, A.; Xiang, Q.L.; Ismail, W.N.A.W.; Chung, S.L.; Lai, Y.M.; Roselee, M.H.; Nur Islami, .; Nyein, K.K.; Hassan, M.H.A.; Bakar, M.F.A.; et al. (Indian Academy of Sciences, 2014)
The granitic rocks of the peninsula have traditionally been divided into two provinces, i.e., Western and Eastern provinces, corresponding to S- and I-type granite respectively. The Western Province granite is characterised by megacrystic and coarse-grained biotite, tin-mineralised, continental collision granite, whereas, the Eastern Province granite is bimodal I-type dominated by granodiorite and associated gabbroic of arc type granite. This paper reports the occurrence of an A-type granite from peninsular Malaysia. The rocks occur in the Besar, Tengah, and Hujung islands located in the southeastern part of the peninsula. The granite is highly felsic with SiO2 ranging from 75.70% to 77.90% (differentiation index = 94.2–97.04). It is weakly peraluminous (average ACNK =1.02), has normative hypersthene (0.09–2.19%) and high alkali content (8.32–8.60%). The granites have many A-type characteristics, among them are shallow level of emplacement, high Ga, FeT/MgO and low P, Sr, Ti, CaO and Nb. Calculated zircon saturation temperatures for the Besar magma ranging from 793 ∘ to 806 ∘C is consistent with high temperature partial melting of a felsic infracrustal source which is taken as one of the mechanisms to produce A-type magma. The occurrence of the A-type granite can be related to the extensional back arc basin in the Indo-China terrane during the earliest Permian.